Study of the 71Π u state of sodium dimer by polarisation labelling spectroscopy. (18th October 2022) - Kowalczyk, P.; Grochola, A.; Jastrzebski, W.
Abstract : Two-colour polarisation labelling experiment measuring excitation spectra of Na 2 in the spectral range 34, 600−39, 400 cm − 1 has furnished observation of the previously unknown 7 1 Π u electronic state. The excited state is characterised by a set of Dunham coefficients describing the f parity levels up to vibrational level v  = 28 and the corresponding potential energy curve is constructed by the inverted perturbation approach method. Molecular parameters determined in the fit include T e = 36583.86 ± 0.03 cm − 1, ω e = 107.50 ± 0.03 cm − 1 and R e = 3.640 ± 0.001 Å. GRAPHICAL ABSTRACT: UF0001